Cruise and container shipping companies: a comparative analysis of sustainable development goals through environmental sustainability disclosure. Issue 2 (17th February 2021) - Di Vaio, Assunta; Varriale, Luisa; Lekakou, Maria; Stefanidaki, Evangelia
ABSTRACT: The shipping industry, due to the ships' gigantism trend and the concentration of operations in specific regions, is considered the source of both positive and negative impacts for port-cities. The ambitious objective of the International Maritime Organization (IMO) for the decarbonisation of the sector till 2050 has further shifted attention on the activities and policies that shipping companies adopt and implement not only for complying with international regulations but moving beyond, integrating sustainability priorities and goals into their corporate strategic planning. In the context of the 17 Sustainable Development Goals (SDGs) of the United Nations, this paper aims at investigating the nature and orientation of voluntary disclosure practices and environmental sustainability for achieving the SDGs in the maritime industry, focusing on the cruise and container shipping markets. Analysis confirms the companies' commitment towards meeting the 2030 Agenda through dedicated sustainability strategies. However, it revealed the qualitative nature of reported information and the lack of specific indicators for measuring and evaluating sustainability performance at the corporate level.